Implementasi Program Indonesia Pintar (PIP) Di Sekolah Menengah Pertama Negeri O1 Kecamatan Dedai Kabupaten Sintang - Lestari, Yuni; Yohanes, Yulius; Rupita, Rupita (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to determine how the implementation of the Smart Indonesia Program (Pip) (Case Study at Sekolah Menengah Pertama Negeri 1 Dedai ) Dedai Regency. Since the reformation era and the enactment of the regional autonomy law, namely Law Number 22 of 1999 concerning regional government, and Law Number 25 of 1999 concerning financial balance between the center and regions (now being refined into Law Number 23 of 2014). The objectives to be achieved in this study are: To determine the process of implementing the Smart Indonesia Program at Sekolah Menengah Pertama Negeri 1 Dedai (PIP-SMP) Dedai Regency. The organization in proposing PIP recipients, which often occurs when duplicate data is submitted to the sekolah and to be included in the system, is a problem because there are still many separate proposals that do not meet the criteria that should receive PIP assistance. Interpretation in distribution for PIP recipients always faces obstacles such as the transfer of financial institutions / banks that collaborate with the government for disbursement of PIP recipient funds so that it requires a fairly long process for each transfer.